Solvent effects in furofuran lignans revealed by vibrational CD spectroscopy - Lee, Eric Y.; Sousa, Victor M.S.; Mestriner, Eloá R. [UNESP]; Bernardino, Kalil; Nascimento, Isabele R. [UNESP]; Batista, João M. (Royal Society of Chemistry (RSC), 2025)
Furofuran lignans are important chiral secondary metabolites widely distributed in the plant kingdom. Despite extensive biological potential, their absolute configuration assignments are mostly based on empirical comparisons of OR values and ECD spectra obtained for structurally related molecules. Since the main structural differences among furofuran lignans reside on the substitution patterns of the chromophoric aromatic moieties, as well as their relative orientations, this approach is risky and the reported stereochemical assignments require independent verification. Herein, a combination of experimental and theoretical vibrational circular dichroism (VCD) spectroscopy was used to investigate the stereochemistry of furofuran lignans isolated from Aristolochiaceae species. Besides providing unambiguous assignments of the absolute configurations of the target lignans, the combination of VCD, molecular dynamics (MD) and QM/MM calculations revealed that key spectral features in acetonitrile solution were reproduced only in the presence of explicit solvent molecules. While that would be expected for molecules containing H-bond donor groups, such as phillygenin (1), the same trend was observed for compounds devoid of H-bond interactions with the solvent (epieudesmin 2 and eudesmin 3). The inclusion of explicit solvation was found to be critical for the stabilization of dihedral angles that allow for proper normal mode coupling and correct reproduction of experimental data. Given that the IR and VCD spectra of the lignans obtained in chloroform solutions were almost superimposable to those recorded in acetonitrile, the conformational stabilization described above and the requirement for explicit solvation would not be restricted to acetonitrile.